2021
DOI: 10.1007/s10811-021-02591-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced response in algal cell surface properties and behaviour: an experimental approach

Abstract: Microalgae are considered an accurate indicator of ecosystem perturbations induced by global climate change. The present work aims to investigate the alteration of temperature on surface properties and behaviour of three algal species using the complementary surface methods (electrochemical and atomic force microscopy). The results showed that the temperature-induced response of algae is species-specific due to the structural features of the cell envelope. Wall-less algae experience the largest nanomechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Another important property of the cell surface that may change, depending on growth conditions, is the rigidity of the cell wall. Indeed, several studies have shown that a specific stress or a change in environmental conditions (such as a change in pH, temperature, or salinity) can have an important effect on the composition or remodeling of the cell wall, thereby changing its nanomechanical properties [60][61][62][63][64][65][66]. Our nanoindentation measurements, performed on C. closterium cells exposed to nanoplastics, showed a significant decrease in cell wall rigidity compared to cells grown without nanoplastics (Figure 7).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Another important property of the cell surface that may change, depending on growth conditions, is the rigidity of the cell wall. Indeed, several studies have shown that a specific stress or a change in environmental conditions (such as a change in pH, temperature, or salinity) can have an important effect on the composition or remodeling of the cell wall, thereby changing its nanomechanical properties [60][61][62][63][64][65][66]. Our nanoindentation measurements, performed on C. closterium cells exposed to nanoplastics, showed a significant decrease in cell wall rigidity compared to cells grown without nanoplastics (Figure 7).…”
Section: Discussionmentioning
confidence: 68%
“…A change in the Young modulus of cells was also observed when the pH of the culture medium changed, and it increased significantly at a higher pH [61]. In addition, previous studies by our group [64,65,68] have shown that the exposure of cells to temperature stress, salinity stress, and cadmium causes changes in cell rigidity, as a consequence of a molecular modification to the cell barrier. It is therefore not surprising that exposure to nanoplastics also alters the nanomechanical properties of cells.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, Novosel et al (2022) employed AFM to examine how temperature affected Dunaliella tertiolecta, Tetraselmis suecica and Cylindrotheca closterium. The results revealed that all three algae maintained their shape at different temperatures and exhibited no distinctive morphological changes at the cell surface.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…Studying algal cell morphology was facilitated by AFM, which does not require a vacuum environment for imaging, unlike electron microscopy. This renders it possible to image cells that do not retain their morphology under a vacuum environment [24].…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…Our recent studies have shown that the adaptive response of microalgae to stress is speciesspecific and stressor-dependent. It seems that diatoms are more resistant to changes in temperature and salinity, with the cell wall having an important protective function in contrast to naked flagellates [25,26]. The adaptive response of microalgae exposed to drops in salinity or in temperature is manifested by an increase in cell stiffness or a change in hydrophobicity due to changes at the molecular level.…”
Section: Introductionmentioning
confidence: 99%